Pasteurella multocida Serotype D Infection Induces Activation of the IL-17 Signaling Pathway in Goat Lymphocytes - Yujing Fu; Yong Meng; Hejie Qian; Taoyu Chen; Xiangying Chen; Qiaoling Chen; Hongyan Gao; Churiga Man; Li Du; Si Chen; Fengyang Wang (Microorganisms)
(1) Background: Pasteurellosis is a global zoonotic bacterial disease, which has caused significant economic impacts in animal husbandry. Nevertheless, there is limited understanding of the immune response between goat peripheral blood lymphocytes (PBLs) and goat-derived Pasteurella multocida (P. multocida). (2) Methods: To investigate the immune response of host PBLs during infection with P. multocida type D, we established an in vitro cell model utilizing isolated primary goat PBLs. Utilizing this in vitro infection model, we employed an enzyme-linked immunosorbent assay (ELISA) to assess the cytokine profile variation in goat PBLs following infection. Meanwhile, RNA sequencing and quantitative PCR (qPCR) methods were employed to analyze the gene expression profile. (3) Results: The ELISA test results indicated that the expression levels of pro-inflammatory cytokines, such as IL-6, IFN-γ, CXCL10, and IL-17A, were significantly elevated within 12 h after infection with P. multocida. In contrast, the levels of the anti-inflammatory cytokine IL-10 were found to be reduced. RNA sequencing and functional enrichment analysis identified 2114 differentially expressed genes (DEGs) that were primarily associated with cytokine-cytokine receptor interactions, viral protein-cytokine interactions, and the IL-17 signaling pathway. Furthermore, protein-protein interaction (PPI) network analysis and qPCR highlighted CD86, CCL5, CD8A, CXCL8, CTLA4, TNF, CD274, IL-10, IL-6, CXCL10, IFNG, and IL-17A that were crucial for the response of PBLs to P. multocida infection. (4) Conclusions: This study systematically revealed the characteristics of PBLs in goats following infection with goat-derived P. multocida type D through the analysis of cytokines and gene expression, providing important theoretical insights for a deeper understanding of the defense mechanisms in goats against P. multocida.